Employment outcome four years after a severe traumatic brain injury: results of the Paris severe traumatic brain injury study. Issue 18 (28th August 2018) - Ruet, Alexis; Jourdan, Claire; Bayen, Eléonore; Darnoux, Emmanuelle; Sahridj, Dalila; Ghout, Idir; Azerad, Sylvie; Pradat Diehl, Pascale; Aegerter, Philippe; Charanton, James; Vallat Azouvi, Claire; Azouvi, Philippe
Abstract: Objective: To describe employment outcome four years after a severe traumatic brain injury by the assessment of individual patients' preinjury sociodemographic data, injury-related and postinjury factors. Design: A prospective, multicenter inception cohort of 133 adult patients in the Paris area (France) who had received a severe traumatic brain injury were followed up postinjury at one and four years. Sociodemographic data, factors related to injury severity and one-year functional and cognitive outcomes were prospectively collected. Methods: The main outcome measure was employment status. Potential predictors of employment status were assessed by univariate and multivariate analysis. Results: At the four-year follow-up, 38% of patients were in paid employment. The following factors were independent predictors of unemployment: being unemployed or studying before traumatic brain injury, traumatic brain injury severity (i.e., a lower Glasgow Coma Scale score upon admission and a longer stay in intensive care) and a lower one-year Glasgow Outcome Scale–Extended score. Conclusion: This study confirmed the low rate of long-term employment amongst patients after a severe traumatic brain injury. The results illustrated the multiple determinants of employment outcome and suggested that students who had received a traumatic brain injury were particularly likely to be unemployed, thus we propose that they may require specific support to help them find work. Implications for rehabilitation: Traumatic brain injury is a leading cause of persistent disablity and can associate cognitive, emotional, physical and sensory impairments, which often result in quality-of-life reduction and job loss. Predictors of post-traumatic brain injury unemployment and job loss remains unclear in the particular population of severe traumatic brain injury patients. The present study highlights the post-traumatic brain injury student population require a close follow-up and vocational rehabilitation. The study suggests that return to work post-severe traumatic brain injury is frequently unstable and workers often experience difficulties that caregivers have to consider.